This is our city! Urban communities re-appropriating their city. - Avram, Gabriela (Springer Open, 2019)
In this chapter, the author examines a citizen-driven intervention regarded as "city hacking"; the initiative empowered citizens to organize themselves around a communal issue and enact urban interventions at economic, social, environmental, and cultural levels. Using a formula created for a TV show that provided scaffolding and brought the community together in a very short interval of time as starting point, during the development the formula was hacked and appropriated in a convenient way, shifting from the expected support of broadcast media to an assemblage of social media tools fit for the purpose. The lived experience and the concrete results demonstrated to the local authorities the value of openness, collaboration with local communities of volunteers, and social media usage. This development provides an example of top-down curation of bottom-up city-making initiatives, opening the way toward hackable institutions. Scaffolding community initiatives through creating flexible formulas anchored in social media channels that are easy to appropriate and adapt are presented as a promising avenue to investigate further.
Keywords: Stadtsoziologie; Digitale Medien; Partizipation; Stadtgesellschaft; Stadtgestaltung; Interaktion